A Niobium Oxyiodate Sulfate with a Strong Second‐Harmonic‐Generation Response Built by Rational Multi‐Component Design - Tang, Hong‐Xin; Zhang, Yu‐Xiao; Zhuo, Chao; Fu, Rui‐Biao; Lin, Hua; Ma, Zu‐Ju; Wu, Xin‐Tao (Angewandte Chemie International Edition, 2019)
A novel niobium oxyiodate sulfate, Nb2O3(IO3)2 (SO4), was fabricated by a rational multi‐component design under moderate hydrothermal conditions. This multi‐component design is inspired by an interesting niobium oxysulfate reaction, which opens a new door for synthetic method to effectively introduce refractory metals such as Nb into crystal structures by hydrothermal synthesis. Nb2O3(IO3)2(SO4) features a cube‐like topological structure with a large phase‐matching second harmonic generation (SHG) response (6×KDP), a wide transparency window (0.38–8 μm), and a high laser damage threshold (LDT) (20×AgGaS2). It has the highest thermostability (stable up to 580 °C under air) among reported non‐centrosymmetric (NCS) iodates and sulfates and is stable in water and even concentrated H2SO4. Furthermore, Nb2O3(IO3)2(SO4) is a unique nonlinear optical (NLO) material among iodates and sulfates, because its SHG effect is mainly caused by the MO6 units rather than the IO3 or SO4 units, which is demonstrated by density functional theory (DFT) calculations. Oh my‐obium! The synthesis of crystalline Nb2O3(IO3)2(SO4) under moderate hydrothermal conditions is reported. The highly thermostable crystal features a strong second‐harmonic‐generation response, a wide transparency window, and a high laser damage threshold.